2004
DOI: 10.1111/j.1067-1927.2004.12610.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental induction of heterotopic bone in abdominal implants

Abstract: Induction of bone tissue requires three elements: osteoprogenitor cells, osteoinductive factors, and a supporting extracellular matrix. In this study, we report on an experimental model in dogs of heterotopic bone tissue production, based on the integration of these osteo-inductive factors into abdominal implants. The implants consist of either a type I collagen sponge wrapped with periosteum and omentum or a type I collagen sponge embedded with demineralized bone powder, platelet-rich plasma, thrombin, and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 31 publications
(38 reference statements)
2
15
0
5
Order By: Relevance
“…Further, polymerized collagen has been shown to have a regenerator effect in experimental induction of heterotopic bone and scleroderma skin lesions [13, 28]. Our findings are in agreement with those studies, for patients under treatment with polymerized-type I collagen who showed lower percentage of IL-1 β - and TNF- α -producing peripheral cells and higher number of IL-10- and Foxp3-expressing cells compared with placebo-treated group.…”
Section: Discussionsupporting
confidence: 92%
“…Further, polymerized collagen has been shown to have a regenerator effect in experimental induction of heterotopic bone and scleroderma skin lesions [13, 28]. Our findings are in agreement with those studies, for patients under treatment with polymerized-type I collagen who showed lower percentage of IL-1 β - and TNF- α -producing peripheral cells and higher number of IL-10- and Foxp3-expressing cells compared with placebo-treated group.…”
Section: Discussionsupporting
confidence: 92%
“…A heterotopic bioassay [21,22] was used to test the osteoinductive activity of CS-Platelet (Fig. 2).…”
Section: Methodsmentioning
confidence: 99%
“…The combination of a collagen type I sponge embedded with demineralized bone powder, PRP, and activation factors (CaCl 2 and thrombin) wrapped with autologous omentum and periosteum induced the high expression of osteoinductive cytokines (TGF- β , BMP-2, and BMP-4) in macrophages, endothelial cells, osteoblasts, osteoclasts, and the local mesenchymal tissue. The combination of these factors within a collagen sponge has the potential to produce mature trabecular bone upon implantation [112]. Although these composite PRP collagen sponges have varying results, none of them have negative effects on bone regeneration which still support the use of these sponges as an alternative bone graft substitute replacing the need for autologous bone harvesting.…”
Section: Hydrogels and Spongesmentioning
confidence: 99%